New pelomedusoid turtles from the late Palaeocene Cerrej?on Formation of Colombia and their implications for phylogeny and body size evolution (2012)
Pelomedusoides comprises five moderate-sized extant genera with an entirely Southern Hemisphere distribution, but the fossil record of these turtles reveals a great diversity of extinct taxa, documents several instances of gigantism, and indicates a complex palaeobiogeographical history for the clade. Here, we report new pelomedusoid turtle fossils from the late Palaeocene Cerrejón Formation of Colombia. The most complete of these is represented by a large skull (condylobasal length = 16 cm) and is described as Carbonemys cofrinii gen. et sp. nov. (Podocnemidae). Carbonemys is incorporated into a parsimony analysis utilizing a modified morphological character matrix designed to test relationships within Panpelomedusoides, with the addition of molecular data from seven genes (12S RNA, cytochrome b, ND4, NT3, R35, RAG-1 and RAG-2) drawn from previous studies of extant Podocnemidae. C. cofrinii is recovered within Podocnemidae in the results of both morphology-only and combined morphological and molecular (total evidence) analyses. However, molecular data strongly impact the inferred relationships of C. cofrinii and several other fossil taxa by altering the relative positions of the extant taxa Peltocephalus and Erymnochelys. This resulted in C. cofrinii being recovered within the crown clade Podocnemidae in the morphology-only analysis, but outside of Podocnemidae in the combined analysis. Two Panpodocnemid turtle taxa of uncertain affinities are represented by new diagnostic shell material from the Cerrejón Formation, though we refrain from naming them pending discovery of associated cranial material. One of these shells potentially belongs to C. cofrinii and represents the second largest pleurodiran turtle yet discovered. Analysis of pelomedusoid body size evolution suggests that climatic variation is not the primary driver of major body size changes. Cerrejón turtles also demonstrate that at least two major subclades of Podocnemidae were already in place in the neotropics by the Early Cenozoic.